PSYCHOLOGICAL ANALYSIS IN NOVEL “YOU’VE REACHED SAM” BY DUSTIN THAO - Puji Adi Pertiwi; Nia Kurniati; jovanka, Novalizcitra; Milatun khasanah; Riska Mauliana (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2025)
This analysis delves into the psychological traits of the characters in Dustin Thao's novel,